THE ALLEGORY USED IN GULHANIY’S WORK “ZARBULMASAL” - Kodirova Vazira Sanjarbek kizi; Bakhtiyorova Maftuna Bakhtiyorovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. The allegory is a prominent literary device used to convey complex moral and social meanings through symbolic figures and narratives. In the work "Zarbulmasal" by the Uyghur poet Gulhaniy, allegory plays a crucial role in expressing ethical values and social criticism in an accessible manner. This article examines the function of allegory in "Zarbulmasal," analyzing its themes, narrative techniques, and cultural significance. Through allegorical imagery, Gulhaniy delivers messages about justice, honesty, wisdom, and human values that remain relevant across time.